Poligami Dalam Perspektif Hadits Bukhari Dan Pasal 3 Ayat (1) UU No. 1 Tahun 1974 Tentang Perkawinan - Milda Kurnia Herawati; Tajul Arifin (Al Fuadiy Jurnal Hukum Keluarga Islam, 2024)
Polygamy is a complex and controversial issue in Islam and law in Indonesia. On the one hand, several Bukhari hadiths touch on polygamy, which some people interpret as a form of divine dispensation. On the other hand, Article 3 paragraph (1) of Law no. 1 of 1974 concerning Marriage firmly adheres to the principle of monogamy. This abstract discusses how polygamy is understood in the Bukhari Hadith and compares it with the principle of monogamy in the Marriage Law. First, this abstract examines Bukhari's hadiths that are relevant to polygamy, taking into account the context and interpretation. Second, this abstract analyzes Article 3 paragraph (1) of the Marriage Law and its relevance to polygamy in the Indonesian social and cultural context. This abstract shows that there are different interpretations of Bukhari's hadiths regarding polygamy. The principle of monogamy in the Marriage Law reflects the values of gender equality and justice in marriage. In-depth and contextual analysis is needed to understand polygamy in Islam and its relevance to law in Indonesia.